Irrational Use of Selected Herbal Medicines During Pregnancy: A Pharmacoepidemiological Evidence From Yemen - Ahmed, Mansoor; Hwang, Jung Hye; Ali, Mohammed Nasr; Al-Ahnoumy, Shafekah; Han, Dongwoon (Frontiers in Pharmacology, 2022)
Background: Recent research indicates irrational use of herbal medicines (HM) during pregnancy that can be harmful to mother and development of baby. However, no study has been conducted to explore the use of HM among pregnant women in a conflict region. Methods: This was a cross-sectional research conducted in the months of July and August in year 2017, at three hospitals in Sana'a, Yemen. Postpartum women were interviewed via the structured instrument to collect data on patterns of HM used during pregnancy. Results: Three hundred postpartum women participated in the study, with 59.3% (178) of them using at least one modality of HM in previous pregnancy. Cinnamon (Cinnamomum verum L), Ginger (Zingiber officinale Z), Barley (Hordeum vulgare P), and Garlic (Allium sativum A) were the most commonly used HM. Statistical analysis showed that consumers of HM had higher rate of caesarian section, and complications during and after the delivery. Conclusions: Consumption of HM during pregnancy was high including contraindicated modalities such as Cinnamon (Cinnamomum verum L) and Barley (Hordeum vulgare P). Use of potentially harmful modalities and association with complications pose a threat to the wellbeing of mothers and newborns. Further studies in this area will be helpful to generate evidence for rational use of HM during pregnancy.